Arbitrarily High-Order (Weighted) Essentially Non-Oscillatory Finite Difference Schemes for Anelastic Flows on Staggered Meshes (Communications in Computational Physics, 2021)
We propose a WENO finite difference scheme to approximate anelastic flows,and scalars advected by them, on staggered grids. In contrast to existing WENOschemes on staggered grids, the proposed scheme is designed to be arbitrarily high-order accurate as it judiciously combines ENO interpolations of velocities with WENOreconstructions of spatial derivatives. A set of numerical experiments are presentedto demonstrate the increase in accuracy and robustness with the proposed scheme,when compared to existing WENO schemes and state-of-the-art central finite difference schemes.